Intra-host dynamics and co-receptor usage of HIV-1 quasi-species in vertically infected patients with phenotypic switch - Fernández, María Florencia (2019)
HIV-1 infection through vertical transmission provides a good model to evaluate intra-host viral evolution and allows to gain insight into the dynamics of viral populations. Our aim was to assess the diversity and dynamics of X4- and R5-using HIV-1 variants in vertically infected children who presented a switch in SI/ NSI phenotype in MT-2 cell assays during chronic infection. Through molecular cloning and next generation sequencing of the C2-V5 env fragment, we investigated HIV-1 evolution and co-receptor usage based on V3 loop prediction bioinformatic tools of longitudinal samples obtained from 4 children. In all cases, the phylogenetic relationships were assessed by Maximum-Likelihood trees constructed with MEGA 6.0. In two cases, V3 loop sequences predicted exclusively R5-using and or X4-using strains, while in another two a higher degree of concordance was observed between the phenotypic and genotypic characteristics. In 3 of the 4 cases, C2-V5 env sequences from different time points were intermingled in phylogenetic trees, with no segregation neither by time or tropism. In only one case monophyletic clustering defined groups of sequences with different co-receptor usage. Comparison of amino acid frequency between isolates with SI and NSI phenotype allowed the identification of 9 possible genetic determinants in subtype F C2-V5 region of env associated to SI/ NSI phenotype in these patients, one of which had previously been reported for subtype B. Overall, we found a low degree of correlation between phenotypic and genotypic properties of HIV-1 quasispecies in patients under chronic infection. Whether HIV-1 subtype or other factors influence the evolution of HIV-1 in vivo will require further research.